Effect of Activator Age on Fly Ash-Based Geopolymer Concrete - Hutajulu, Jacob Hasiholan; Faisal, Faisal; Herwani, Herwani; Parabi, Ashraf Dhowian (Jurnal Teknik Sipil, 2025)
Geopolymer concrete is a sustainable alternative that replaces Portland Cement (PC) with fly ash. This research aims to analyze the mechanical properties of geopolymer concrete with variations in NaOH solution aging. An experimental method was applied through a series of tests, including slump, compressive strength, split tensile strength, and modulus of elasticity. The results indicate that the slump value ranges from 9,5 cm to 15,5 cm. The bulk density of geopolymer concrete varies between 2.313,052 Kg/m ³ and 2.387,324 Kg/m ³. The maximum compressive strength at 28 days was achieved after a 24-hour NaOH curing period, reaching 15,915 MPa, whereas the minimum strength of 10,186 MPa was observed with no curing time. The highest split tensile strength was observed at 24 hours (1,556 MPa), whereas the lowest occurred at 0 hours (1,085 MPa). Using the Chord Modulus method, the modulus of elasticity reached its highest value at 24 hours (3.625,261 MPa) and its lowest at 48 hours (2.152,499 MPa). Thus, this research concludes that a 24-hour NaOH curing period results in geopolymer concrete with optimal compressive strength and mechanical properties.